PEMBERIAN PAKAN TERBATAS SECARA PERIODIK PADA AYAM PEDAGING (LENGHORN) - Darmawati ' (Program Studi Pendidikan Biologi, 2005)
The research was to examine effect restricted feeding in lenghorn chicken, in Labuh Baru Pekanbaru from June -August 2001. The experiment was conducted using completely Randomized Design ( R A L ) with three replications. The treatment consist of A (Full feeding without the fast), B (Three days full feeding, one day the fast), C (six days full feeding, one day the fast). The treatment each consist of five lenghorn chickens Various parameter such as food consume, increase body weight and food conversion. Data were analyzed using Anava with DMRT 5 % level of signification. The result o f this experiment showed that effect restricted feeding significance to food consume, increase body weight and food conversion in lenghorn chicken. The treatment C, was good to increase body weight and food conversion, where as the treatment B to food consume. Key words : Consume, Conversion, lenghorn chicken, restricted feeding